ERect of eo-inoeulum of white-rot fungus (Phonerochaefe ehrysosporium) and cellulolytic baetesimm (Gellulonmoncas celEuEans) on paddy straw corngosting* - MISHRA, BRIJESH KUMAR; LATA, LATA (The Indian Journal of Agricultural Sciences, 2011)
Composting of agricultural residues is a biochemical phenomenon mediated by various microorganisms present in soil and plant residues. Hyper lignolytic and cellulolytic microorganisms are reported to activate the composting process. Therefore an investigation was carried out during 2004-2005 to assess the performance of white rot fungi (Phmerochaete chrysosporium) and cellulolytic bacterium as activator for paddy straw composting. Paddy straw amended with poultry manure (12.5% w/w) or urea (0.5%) was cornposted in open pits. A co-inoculum of Phanerochaete chrysosporium MTCC787 / E chrysosporium NCIM 1073 and Cellulomor~as cellulans MTCC23 was used. Compost samples were analyzed for organic matter, humus content and C: N ratio at monthly intervals for three months. Highest humus was recorded after third month of composting. Organic matter and C: N ratio of paddy straw compost was within permissible limits for use in field crops.